Nutrient losses of agricultural land due to brick manufacturing in the central region of Bangladesh - Rahman, MK; Eunuch, M; Haque, GM Fazlul; Khan, HR; Rouf, AJM Abdur (Dhaka University Journal of Biological Sciences, 2015)
Nutrient losses due to brick production were evaluated at 50 Upazilas in nine districts of the central region of Bangladesh. The average land area occupied by a brick kiln was 0.59 ha. Water‐ extractable N, P, K and S, and total N, P, K and S decreased by 67, 60, 62, 53, 67, 67, 87 and 33% in burnt bricks compared to unburnt one, respectively. Permanent loss of huge quantity of plant nutrients is occurring due to brick manufacturing every year in Bangladesh. Dhaka Univ. J. Biol. Sci. 24(1): 53-57, 2015 (January)